Fertility Estimation Using the Own Children Method in South Sulawesi Province in 2021 - Sri Nur Bayani Nur; Veni Hadju; Mansyur Radjab (Populasi, 2022)
The unavailability of data regarding current fertility conditions complicates the photograph population conditions, especially after the Covid-19 pandemic in South Sulawesi Province. This study aims to produce an estimate of the fertility rate at the district/city level in South Sulawesi Province. Based on the available supporting data, an estimation of the fertility rate in the form of the Total Fertility Rate (TFR) was made using the indirect method, namely the own children method. The calculation is based on the number of women of childbearing age who have ever married and the number of children under five owned by the woman to get the birth rate. Based on these calculations, the results show that all districts/cities in South Sulawesi Province have TFR above the national level. When viewed by region, on the average, districts/cities in the northern part have a higher TFR than districts/cities in the southern part of South Sulawesi Province. With the fertility rate obtained and its distribution, a guideline for the government to formulate appropriate plans and policies is expected as the outcome.